Comprehensive single-cell transcriptomic reveals different destinies of melanocytes and dynamic changes of immune microenvironment in a psychological stress-induced leukoderma and leukotrichia mouse model - Xuechen Cao; Yongkai Yu; Hang Yao; Yujie Zheng; Jiawei Lu; Yifei Feng; Tongxin Pei; Ziyu Li; Ming Lu; Yan Lu (Molecular Medicine)
Abstract Background Vitiligo is an acquired skin depigmentation disorder often accompanied by leukoderma and leukotrichia. Half of vitiligo patients experience episodes of stress. Methods We established a chronic unpredictable mild stimulation (CUMS) model in C57BL/6 J mice to simulate chronic mental stress-induced leukoderma and leukotrichia. Single-cell RNA sequencing was performed to determine the immune landscape and to characterize the relationship between immune-stromal cells. Immunohistochemistry was employed for validation. Results We discovered a similar pro-inflammatory micro-environment composed of keratinocytes and fibroblasts similar to that in human vitiligo. Macrophages in CUMS mice expressed high levels of inflammatory factors and were inclined to an M1 pro-inflammatory phenotype. Two distinct clusters of melanocytes were also identified: Mel2, defined as melanocyte stem cells, and Mel3, defined as mature melanocytes. Mel2 cells were prone to pyroptosis and necroptosis, while Mel3 cells were susceptible to oxidative stress, mitochondrial dysfunction, and ferroptosis. Compared with control mice, higher expression of CXCL16 on dendritic cells and of the CXCL16 ligand, CXCR6, on γδT cells were observed in leukoderma. Dendritic cells and natural killer T cells in the CUMS mouse spleen exhibited elevated levels of CXCL16 and CXCR6, respectively. Activation of the CXCL16-CXCR6 axis and a non-specific immune response in our CUMS model might imitate chronic mental stress-induced vitiligo in humans better than CD8 + cytotoxic T lymphocyte-mediated models. Conclusions We discovered two melanocyte clusters with distinct fates and a pro-inflammatory micro-environment with CXCL16–CXCR6 axis activation of antigen-presenting cells and other innate immunocytes that might provide new insights into the pathogenesis of stress-induced vitiligo.